2020
DOI: 10.1111/jcmm.15833
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0007331 knock‐down suppresses the progression of endometriosis via miR‐200c‐3p/HiF‐1α axis

Abstract: Endometriosis is considered a chronic gynaecological disorder with a high prevalence among women of reproductive age, which are usually clinically manifested by acyclic pelvic pain, dyspareunia, dysmenorrhoea and subfertility. 1 Not only that, but endometriosis also increases the risk of other complex diseases such as migraines, painful bladder syndrome and irritable bowel syndrome. 2 As the third leading cause of gynaecologic hospitalization in the United States, the incidence of endometriosis varies from 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Evidences have demonstrated aberrant circRNA expression in endometriosis [5,6]. Some studies showed that circRNAs promote the pathogenesis of endometriosis via miRNAs [7][8][9]. Our further work found that circ_0000673 was signi cantly deregulated in ectopic endomemtrium compared to eutopic endometrium [5].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Evidences have demonstrated aberrant circRNA expression in endometriosis [5,6]. Some studies showed that circRNAs promote the pathogenesis of endometriosis via miRNAs [7][8][9]. Our further work found that circ_0000673 was signi cantly deregulated in ectopic endomemtrium compared to eutopic endometrium [5].…”
Section: Introductionmentioning
confidence: 64%
“…Moreover, our ndings uncover that loss of circ_0000673 could promotes proliferation and migration of endometrial cells. Recent studies suggested that circATRNL1 promotes epithelial-mesenchymal transition(EMT) by regulating Yes-associated protein 1 [23], and high expression of circ_0007331 play a vital role in the proliferation and invasion in endometriosis [9]. The studies suggested the regulation effects of circRNAs in the progression of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that loss of circ_0000673 could promote the proliferation and migration of endometrial cells. Recent studies have suggested that circATRNL1 promotes the EMT by regulating Yes-associated protein 1 28 , and that high expression of circ_0007331 plays a vital role in the proliferation and invasion of cells in endometriosis 10 . These studies suggest that circRNAs play a regulatory role in the progression of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found aberrant circRNA expression in endometriosis [6,7]. Some of these studies showed that circRNAs promote the pathogenesis of endometriosis via regulating the function of miRNAs [8][9][10]. In a previous work, we found that circ_0000673…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation